2019
DOI: 10.1089/vim.2019.0012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Autoantibody to Rods and Rings with Hepatitis C Outcome and Viral Load

Abstract: Despite the current availability of more potent drugs, hepatitis C virus (HCV) infection is still treated with a combination of IFN-a and ribavirin in many countries. Interferon/ribavirin therapy can induce the appearance of autoantibodies to Rods and Rings (anti-RR), which have been associated to a poorer prognosis. The aim of this study was to investigate the prevalence of anti-RR antibodies before and after ribavirin therapy and to look for a possible association with HCV infection outcome. In this context,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…Studies have shown that anti-RR positivity rates range from 14.1% to 38%. 7,19 A study by Alsius et al 20 found that the rate of anti-RR in patients with HCV infection was 9.2% with similar treatment groups, whereas in our study this was 15.16%. In the long-term study of da Silva Sacerdote et al 18 this rate was 23% in patients who had received PEG-IFN/RBV.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Studies have shown that anti-RR positivity rates range from 14.1% to 38%. 7,19 A study by Alsius et al 20 found that the rate of anti-RR in patients with HCV infection was 9.2% with similar treatment groups, whereas in our study this was 15.16%. In the long-term study of da Silva Sacerdote et al 18 this rate was 23% in patients who had received PEG-IFN/RBV.…”
Section: Discussioncontrasting
confidence: 53%
“…PEG‐IFN and RBV were coadministered to all patients who had anti‐RR positivity. Studies have shown that anti‐RR positivity rates range from 14.1% to 38% 7,19 . A study by Alsius et al 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This seems to indicate that anti-RR is a druginduced autoantibody. However, recently some scholars also have found that anti-RR antibodies can exist in patients with hepatitis C before antiviral treatment or non-hepatitis C patients, patients with the therapy of other drugs, and even healthy people (36)(37)(38). The interaction between HCV protein and RR structure may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon/ribavirin therapy can induce the appearance of anti‐RR, which has been associated with a poorer prognosis. Ribavirin‐induced anti‐RR autoantibody seems to be associated with a more frequent nonresponse to IFN‐α/ribavirin(IFN/RBV) therapy with a significantly higher HCV viral load 7 …”
Section: Introductionmentioning
confidence: 99%